Influence of soil types with different soil-forming process on the qualitative and quantitative detection of microplastics by near-infrared spectroscopy - Linwei Cai; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Sciences, 2026)

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

Influence of soil types defined by soil genesis on the qualitative and quantitative detection of microplastics in soil by mid-infrared spectroscopy - Linwei Cai; Chunxu Wan; Zengling Yang; Zhuolin Shi; Xintong Zhang; Jinzhao Li; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Two key triggers and their mechanisms of the spring rainy season onset over southern China - Kexu Zhu; Wen Chen; Peng Hu; Linwei Jiang; Ruowen Yang; Lixuan Huang; Qingyu Cai; Yongmao Peng; Jingnan Li; Lu Gao; Qi Yan; Yehong Luo (Atmospheric Research, 2026)

Observational climatology and interannual variability of the spring rainy season onset over southern China: Objective definition and influence from tropical Pacific Ocean - Kexu Zhu; Wen Chen; Peng Hu; Yehong Luo; Ruowen Yang; Linwei Jiang; Qingyu Cai; Lu Gao; Jingnan Li; Yongmao Peng; Changhao Wu; Ziqi Niu (Atmospheric Research, 2025)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Thallium release from biochar-amended soil to runoff in laboratory experiments - Lezhang Wei; Dafeng Cai; Fangqing Li; Yu Liu; Linwei Zeng; Dinggui Luo; Xuexia Huang; Tangfu Xiao; Hang Shi; Haiqi Yan (Environmental Pollution, 2023)

Evaluation of intervention effects of dietary coenzyme Q10 supplementation on oxidized fish oil-induced stress response in largemouth bass Micropterus salmoides - Yuexing Zhang; Linwei Cai; Zhiyong Dong; Bowen Wu; Yangyang Gong; Baoping Zhang; Bo Wang; Jiaming Kang; Tianhong Ke; Zhijin Xu; Trond Storebakken; Bo Shi (Fish & Shellfish Immunology, 2023)